ITER first mirror mock-ups exposed in Magnum-PSI. (25th May 2016) - Marot, L.; De Temmerman, G.; van den Berg, M.A.; Renault, P.-O.; Covarel, G.; Joanny, M.; Travère, J.M.; Steiner, R.; Mathys, D.; Meyer, E.
Abstract: The goal of this work was to investigate coated first mirrors under very harsh erosion conditions. Mock-up mirrors were exposed to high-flux hydrogen/argon plasma in the linear plasma facility Magnum-PSI. Rhodium (Rh) and molybdenum (Mo) coated mirrors of different coating thicknesses, with or without water cooling, exhibited different responses to this exposure. Failures of Rh films were demonstrated for 5 micron thick film, 1 micron film revealed 10% decrease in the specular reflectivity only in the exposed area. In comparison, water cooled Mo mock-ups showed a significant diffuse reflectivity on the entire surface leading to more than 50% specular reflectivity losses in the visible range. The losses for non-cooled Mo samples did not exceed 7% in the whole studied wavelength range of 250–2500 nm. Three phenomena were proposed to explain these results. First the mechanical properties of the films as characterized by scratch and hardness measurements as well as residual stress analysis measured by x-ray diffraction. Rh films showed a high compressive stress value of 2.5  ±  0.4 GPa leading to poor adhesion of the thick films deposited on stainless steel substrate due to the high amount of available energy per area stored in the unbuckled film i.e. G 0 > 30 J m −2 . It was confirmed by ANSYS simulation that the von Mises stress for the Rh coating was twice as high as that for the Mo coating due to different mechanical properties. Moreover, the maximum stress for thick Rh film (261 MPa) was higher than the critical buckling stress calculated with a buckle clamped Euler column model demonstrating the failure mode of the film. The second phenomenon was roughening of the mirror surface which was flux and temperature dependent, i.e. at low temperatures the surface would roughen randomly without any oriented surface morphology and at higher temperatures the surface diffusion constants would dominate the process and smoothen the surface. The last phenomenon was the significant oxidation and carbidization of the Mo surface even on the non-exposed area, as detected by x-ray photoelectron spectroscopy, leading also to a decrease in the reflectivity in the entire measured range, which was not observed for Rh film.